2011
DOI: 10.1002/asi.21610
|View full text |Cite
|
Sign up to set email alerts
|

Privacy dictionary: A new resource for the automated content analysis of privacy

Abstract: This article presents the privacy dictionary, a new linguistic resource for automated content analysis on privacyrelated texts. To overcome the definitional challenges inherent in privacy research, the dictionary was informed by an inclusive set of relevant theoretical perspectives. Using methods from corpus linguistics, we constructed and validated eight dictionary categories on empirical material from a wide range of privacy-sensitive contexts. It was shown that the dictionary categories are able to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 37 publications
1
45
0
4
Order By: Relevance
“…In order to check how this issue has been addressed by the area, is aimed to analyze the recent publications on the subject, categorizing them according to the privacy dictionary developed by Vasalou et al(2011). It was observed that the issue has been more heavily treated with respect the issues related to privacy violation, and that such publications are predominantly derived from an international context.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to check how this issue has been addressed by the area, is aimed to analyze the recent publications on the subject, categorizing them according to the privacy dictionary developed by Vasalou et al(2011). It was observed that the issue has been more heavily treated with respect the issues related to privacy violation, and that such publications are predominantly derived from an international context.…”
Section: Introductionmentioning
confidence: 99%
“…As questões de privacidade têm sido discutidas em muitos ambientes, como na mídia, na área de segurança (polícia), e também nas conversas do cidadão comum (VASALOU et al, 2011). Muitos são os aspectos abordados nos estudos desenvolvidos pela temática, aspectos esses relacionados à forma como a privacidade é conseguida por meio de ações de controle, e quais são os possíveis efeitos psicológicos positivos relacionados à privacidade.…”
Section: Introductionunclassified
See 3 more Smart Citations